From Accountability to Assurance – Stakeholder Perspectives in Local Government. Issue 2 (23rd June 2014) - Quinlivan, Dale; Nowak, Margaret; Klass, Des
Abstract : This article reports on research which sought to explore the understanding of accountability for performance amongst constituents of local government in Western Australia. Recent trends to increase the public accountability and financial reporting requirements for local governments underline the need to understand the value and use made of this performance information by local government constituents.